New species and new combination in the genus Plistonax Thomson, 1864 (Cerambycidae, Lamiinae, Acanthoderini) - Silva, José Osvaldo Júnior; Haseyama, Kirstern Lica Follmann; de Santana Souza, Diego (Zootaxa, 2019)
Plistonax Thomson, 1864 is a Neotropical genus of longhorned beetles (Cerambycidae: Lamiinae) currently composed of six species. Herein, we describe a new species (Plistonax albituberculatus Silva Júnior & Souza sp. nov.) from Brazilian States of Rio de Janeiro and Bahia. We also propose the transference of Exalphus hefferni Audureau, 2017 to Plistonax, resulting in the following comb. nov.: Plistonax hefferni (Audureau, 2017).